4(x-4)-1=-5(-5x+5)-7x

Simple and best practice solution for 4(x-4)-1=-5(-5x+5)-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-4)-1=-5(-5x+5)-7x equation:


Simplifying
4(x + -4) + -1 = -5(-5x + 5) + -7x

Reorder the terms:
4(-4 + x) + -1 = -5(-5x + 5) + -7x
(-4 * 4 + x * 4) + -1 = -5(-5x + 5) + -7x
(-16 + 4x) + -1 = -5(-5x + 5) + -7x

Reorder the terms:
-16 + -1 + 4x = -5(-5x + 5) + -7x

Combine like terms: -16 + -1 = -17
-17 + 4x = -5(-5x + 5) + -7x

Reorder the terms:
-17 + 4x = -5(5 + -5x) + -7x
-17 + 4x = (5 * -5 + -5x * -5) + -7x
-17 + 4x = (-25 + 25x) + -7x

Combine like terms: 25x + -7x = 18x
-17 + 4x = -25 + 18x

Solving
-17 + 4x = -25 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
-17 + 4x + -18x = -25 + 18x + -18x

Combine like terms: 4x + -18x = -14x
-17 + -14x = -25 + 18x + -18x

Combine like terms: 18x + -18x = 0
-17 + -14x = -25 + 0
-17 + -14x = -25

Add '17' to each side of the equation.
-17 + 17 + -14x = -25 + 17

Combine like terms: -17 + 17 = 0
0 + -14x = -25 + 17
-14x = -25 + 17

Combine like terms: -25 + 17 = -8
-14x = -8

Divide each side by '-14'.
x = 0.5714285714

Simplifying
x = 0.5714285714

See similar equations:

| (10x^3-18x^2)/2x^2 | | 3+2ab-4ac+6bc= | | 2(x-2)+2x=4 | | (X-19)+17=63 | | -24b=-48 | | 1p^2+2p-24=0 | | 7(b+10)= | | -2/3n-4=5 | | (x+16)(x-18)=180 | | 4x+10=3x-4 | | -2(u+1)=-2(9u-7)+4u | | 3(-2+7x)=-27 | | 1250w^10z^5/20w^2z^2 | | 2z+7=3z-11 | | 1-5x=6x-10 | | 3(u+2)+2u=7(u-1)+1 | | 3x+2(3x+5)-4(3x+4)+3(3x+2)+8=0 | | (8x+8)+(-9x+9)= | | x^2+8y+6x=y^2-18 | | 3(x+4)=-2(3x-14) | | 4/7x2=13 | | 6x+2=46+2x | | 4/7*2=13 | | 22x-7=180 | | 5-2(x-7)=17-2x | | -3.2b+6=-5.1 | | 4(3x-1)=45 | | 2x^2+7=8x | | -5-2x+x=3 | | -2500-4.05=3000 | | -5(x+12)-13-=-24 | | 4.3b+5=8.1 |

Equations solver categories